Preferences of Participants in Public Transport - Nagy, Orsolya Bernadett; Csipkés, Margit; Balogh, Péter (International Journal of Engineering and Management Sciences, 2018)
Today, the number of people who use public transport is decreasing, while the share of private transport is growing steadily. In order for people to choose public transport instead of a more convenient and more flexible individual transport, we need to know the factors that can influence them most in their decisions. In the first part of our article we review the main features of intermodality, intermodal nodes and intermodal public transport. Intermodal integration has to be realized through physical, network, fare, information and institutional level. In order to be able to formulate the integration goals correctly and to operate the entire intermodal system efficiently, we need to know the preferences that most affect the decisions of users of public transport or of nonusers. According to the literature, comfort, prices and travel time, on which people judge the status of public transport.